(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The methods of financing green projects in the activities of commercial banks include various tools and approaches aimed at supporting environmentally sustainable initiatives. Key methods include providing green loans and loans, issuing green bonds, investing in green funds and structured financial products, as well as establishing specialized credit lines and programs. These tools allow banks not only to actively participate in the ecological transformation of the economy but also to act as a catalyst for sustainable development, contributing to reducing the carbon footprint and increasing energy efficiency in various sectors and regions.